Pengembangan Bahan Ajar Pengajaran Tata Krama untuk Universitas Islam berkenaan dengan Krisis Kesopanan pada Gen-Z - Djalaluddin, Mawardi; Uswatunnisa; Nihla Afdaliah (Jurnal Pendidikan dan Pengajaran, 2024)
Rapid social and technological change, which has changed the way of social interaction and communication between generations. Generation Z, who grew up in the digital era, is often more exposed to global values and different cultures through social media and the internet.  The modesty crisis is being experienced by most of generation Z. This fact arouses researchers' curiosity to solve this problem. This research is R&D research using the ADDIE design. Researchers designed and developed syllabi, lesson plans and teaching materials about character and included them in the Aqidah Akhlak course. These products are implemented on one campus. After that, researchers evaluated product use through questionnaires and tests. The subjects in this research are generation Z. The research results are valid, practical and effective in reintroducing and instilling good manners in students. The implications of this research are The findings of this research can encourage the development of a curriculum that is more integrated with etiquette values, so that schools and educational institutions can teach ethics and manners more effectively. The aim of research on Instructional Materials for Manners due to the Politeness Crisis in Gen-Z is to identify and understand the factors that cause a decline in politeness among the younger generation and develop effective learning materials to overcome this problem.